1998
DOI: 10.1177/109442819800100106
|View full text |Cite
|
Sign up to set email alerts
|

A Brief Tutorial on the Development of Measures for Use in Survey Questionnaires

Abstract: The adequate measurement of abstract constructs is perhaps the greatest challenge to understanding the behavior of people in organizations. Problems with the reliability and validity of measures used on survey questionnaires continue to lead to difficulties in interpreting the results of field research. Price and Mueller suggest that measurement problems may be due to the lack of a well-established framework to guide researchers through the various stages of scale development. This article provides a conceptua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

39
3,079
4
75

Year Published

2013
2013
2020
2020

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 2,854 publications
(3,334 citation statements)
references
References 48 publications
39
3,079
4
75
Order By: Relevance
“…Adequate internal consistency reliability was obtained with as few as five items [10]. Hinkin [9] reported that an adequate internal consistency reliabilities can be obtained with as few as three items.…”
Section: B Scale Developmentmentioning
confidence: 96%
See 2 more Smart Citations
“…Adequate internal consistency reliability was obtained with as few as five items [10]. Hinkin [9] reported that an adequate internal consistency reliabilities can be obtained with as few as three items.…”
Section: B Scale Developmentmentioning
confidence: 96%
“…Hinkin [9], [10] highlighted that to satisfactory operationalize a construct with appropriate measures and determine construct validity the best practice scale development follows three basic stages: Item generation, scale development, and scale evaluation.…”
Section: Hinkin's Scale Devlopment Constructionmentioning
confidence: 99%
See 1 more Smart Citation
“…Ao longo da pesquisa bibliográfica realizada para este estudo, não foi identificado na literatura nenhum indicador capaz de medir adequadamente as possíveis dimensões da execução da estratégia. Hinkin (1998) (Hinkin, 1998). Em geral, uma escala que mensura um número máximo de discriminação é mais recomendável que uma escala com poucas categorias, e deve ser preferida para análises de correlação e regressão (Wiswanathan, Sudman e Johnson, 2004).…”
Section: Desenvolvimento De Medidas Para a Operacionalização Do Constunclassified
“…A abordagem dedutiva para listagem de indicadores é baseada em sólida fundamentação teórica e extensa revisão de literatura, enquanto que a abordagem indutiva se baseia nas opiniões ou descrições de especialistas, isto é, de pessoas envolvidas com o fenômeno (Hinkin, 1998 …”
Section: Delineamento Da Pesquisaunclassified